Essays on the Demand-Side Management in Electricity Markets - Ieva Linkeviciute (Copenhagen Business School (CBS), 2019)
This Ph.D. thesis focuses on the demand-side management in electricity markets and a new player in the market lcub an aggregator of exible demand. The thesis consists of three independent chapters investigating the entrance of this new player in the power markets from di erent angles: focusing on the aggregator, a large power consumer and a producer. The rst chapter, of demand-side exibility in electricity markets: the e ects of portfolio choice", analyses the performance of the aggregator depending on its portfolio choice. I have investigated several portfolios of di erent exibility sources: electrical vehi- cles, heat pumps and/or home appliances like washing machines, dryers and dish washers. I have used Nord Pool power market data for Denmark's bidding area DK2 to identify the e ects of the portfolio choice on the imbalance payments and compensations to consumers that provide exibility. The results show that di erent compositions of exibility sources lead to di erent imbalance payments and compensations to consumers. However, there is no signi cant additional value of having an access to all types of exibility sources unless there is a xed contract cost. This suggests that the aggregator would choose to specialise in cer- tain types of exibility sources. Also, I nd that the incentives for consumers to participate in demand-side management programs might be not su cient, since the compensation for the provided exibility is very low.
hdl:10398/9708
Keywords: 650